Extracorporeal Membrane Oxygenation in Severe Acute Respiratory Distress Syndrome Caused by Chlamydia psittaci: A Case Report and Review of the Literature - Wang, Lu; Shi, Zhaokun; Chen, Wei; Du, Xianjin; Zhan, Liying (Frontiers in Medicine, 2021)
Background: Infected by Chlamydia psittaci could lead to serious clinical manifestations in human, including severe pneumonia with rapid progression, adult respiratory distress syndrome, sepsis, multiple organ dysfunction syndrome (MODS), and probably death. Implementation of extracorporeal membrane oxygenation (ECMO) in the patient with severe ARDS gives a promising new method for recovery. Case presentation: We report our successful use of venovenous (VV) ECMO in a 48-year-old man who manifested with severe respiratory distress syndrome, acute kidney injury, and septic shock caused by diagnosed pneumonia. After combination of therapy including anti-infection, mechanic ventilation and continuous renal replacement therapy (CRRT), acute inflammatory syndrome developed. However, his respiratory status rapidly deteriorated. Then veno-arterial (VA) ECMO support was placed on the patient as suddenly slowing of heart rate. Harlequin (“North/South”) Syndrome occurred after ECMO initiation. A series of process could not relieve hypoxia in the upper body. At last, transition to VV-ECMO improved hypoxia. Duration of VV ECMO was 7 days and the mechanic ventilation was weaned the next day. On the day of ECMO weaning, nanopore targeted sequencing (NTS) of bronchoalveolar lavage fluid (BALF) reported the presence of Chlamydia psittaci. After 19-day of critical systemic rehabilitation and combination therapy, the patient fully recovered from Chlamydia psittaci.